Methylphenidate use and misuse among medical residents in Israel: a cross-sectional study - Eden Zahavi; Liat Lev-Shalem; Ilan Yehoshua; Limor Adler (BMC, 2023)
Abstract Background Methylphenidate (MPH) and other stimulants may be misused, mainly as cognitive enhancers and recreational drugs. Data regarding misuse among medical residents are scarce. This study aimed to evaluate the prevalence of and main reasons for methylphenidate (MPH) use and misuse among Israeli medical residents. Methods In this cross-sectional study, we sent an online questionnaire to medical residents who had completed their first residency exam and specialists with up to 2 years of experience. We asked about the use of MPH before and during residency and attitudes toward the use of MPH as a cognitive enhancer. We also added the Adult ADHD Self-Report Scale (ASRS) questionnaire, a validated tool used to screen for the presence of attention deficit hyperactivity disorder (ADHD). Users and misusers were classified based on self-report of use and formal ADHD diagnosis. Logistic regression analysis was used to evaluate factors associated with MPH misuse. Results From March 2021 to August 2021, 370 physicians responded to our questionnaire (response rate 26.4%). Twenty-eight met the exclusion criteria and were not included. The respondents' average age was 36.5 years. Women comprised 63.5% of the respondents. Of the participants, 16.4% were classified as users and 35.1% as misusers. The prevalence of misusers was 45.6% among surgery and OB/GYN physicians, 39.4% among pediatricians and internists, and 24% among family physicians (P < 0.001). Misusers had a more liberal approach than others to MPH use as a cognitive enhancer. Factors associated with misuse of MPH included not being a native-born Israeli (OR-1.99, 95% CI 1.08, 3.67) and type of residency (OR-2.33, 95% CI 1.22, 4.44 and OR-4.08, 95% CI 2.06, 8.07 for pediatrics and internal medicine and surgery, respectively). Conclusion Very high levels of MPH misuse during residency may be related to stress, long working hours, night shifts, and the academic burden of the residency period. We believe that our findings should be considered by healthcare policymakers as they make decisions regarding the conditions of medical residencies. The use of MPH as a cognitive enhancer should be further studied and discussed.